Integrate:

`int` `(sqrt(x)/(x^2+x))`

` `

` `

` `

### 1 Answer | Add Yours

Let ;

`x = tan^2t`

`dx = 2tantsec^2tdt`

`sqrtx/(x^2+x) `

`= (sqrt(tan^2t))/(tan^4x+tan^2t)`

`= (tant)/(tan^2t(1+tan^2t))`

`= 1/(tantsec^2t)`

`intsqrtx/(x^2+x)dx`

`= int1/(tantsec^2t)xx2tantsec^2tdt`

`= int2dt`

`= 2t+C` Where C is a constant.

`= 2tan^(-1)sqrtx+C`

** So the answer is** `intsqrtx/(x^2+x)dx = 2tan^(-1)sqrtx+C`

**Sources:**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes